Entrepreneurship Narration in Sandiaga Uno’s Instagram : A Study on 2019 Presidential Election Campaign: (A Study on 2019 Presidential Election Campaign) - Lubis, Putri Handayani; Puspitasari, Maria (Jurnal Entrepreneur dan Entrepreneurship, 2021)
Entrepreneurship often becomes an alternative profession, while in fact, being an entrepreneur is a strategic choice which is ideally based on strong determination and belief that it is able to change the quality of life. Sandiaga Uno used entrepreneurship narration during the 2019 presidential election campaign in his social media in order to influence the youth. The present study aimed to explore Sandiaga Uno’s entrepreneurship narration on Instagram and to identify the narration in influencing young people during the 2019 presidential election campaign. This study was categorized as qualitative research with thematic analysis. The result of the study found that Uno’s campaign narration focused more on hopes. His narration of entrepreneurship focused on motivating the Millenials without explaining further about the risk of being an entrepreneur and how to fund and maintain a business. Uno utilizes his background as an entrepreneur by motivating his campaign. Uno also invited celebrities and several Actors who have businesses to motivate young people to become entrepreneurs. Risk management needed in an entrepreneur because many entrepreneurs are not prepared to deal with risk so the business that was built cannot last. Likewise, there are still many entrepreneurs who cannot make the most of existing technology to develop its business because of its capacity.